Experimental study on grout diffusion patterns and reinforcement effect of sand stratum based on laboratory tests - Haotian Guo; Yinglian Sun; Xinzhu Zhao; Chao Sun; Runjian Zhou (AIP Advances)
To investigate the diffusion and reinforcement effects of different slurries in the sand stratum, the grouting reinforcement simulation laboratory test system was developed. Ordinary Portland cement (OPC), fly ash Portland cement (FPC), and early strength agent Portland cement (ESAPC) slurries were selected as grouting materials to analyze the effects of water–cement ratio, fly ash content, and injection pressure on the maximum diffusion radius. A uniaxial compressive strength test was conducted to analyze the effect of different slurries in reinforcing sand. A scanning electron microscope was used to reveal the microscopic sand-slurry cementation reinforcement mechanism and differences of different materials on sand reinforcement. The results show that all three materials diffuse through the sandy soil during the injection and reinforce it to varying degrees. FPC slurry has the largest diffusion radius. ESAPC slurry and OPC slurry are the next largest. Increasing the water–cement ratio and injection pressure can improve the diffusion radius of the slurry, but once the grout amount reaches a certain point, the effect of further pressurization is no longer significant. ESAPC slurry substantially increases the early compressive strength of the consolidated material. The reinforcement effect of all three slurries decreases with increasing water–cement ratio. ESAPC exhibits a higher degree of sand-slurry cementation than OPC and FPC, so it is more suitable for early consolidation and water interception in water-rich sand stratum. The concept of “saturated slurry content” is proposed. The research provides a theoretical basis for slurry configuration and selection in sand grouting projects.